2002
DOI: 10.12968/bjon.2002.11.8.10165
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine reduction education to improve urinary symptoms

Abstract: Caffeine reduction is an internationally accepted treatment strategy for patients with urinary symptoms. However, there is little trial evidence in support of a caffeine/urinary symptom effect. A prospective randomized trial was conducted among 95 consecutive adult patients with urinary symptoms presenting to two nurse continence advisers. Frequency, urgency and leakage outcomes were tested 1 month postenrolment. Trial findings indicate that caffeine intake was reduced (P<0.0001) in the experimental group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 7 publications
3
67
0
9
Order By: Relevance
“…These results are similar to Bryant et al 12 where, following instruction, participants were able to significantly reduce caffeine intake compared to controls. In the current study, although the selfmonitoring group received instruction to increase fluid intake if their intake was inadequate, the change was similar in both groups.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to Bryant et al 12 where, following instruction, participants were able to significantly reduce caffeine intake compared to controls. In the current study, although the selfmonitoring group received instruction to increase fluid intake if their intake was inadequate, the change was similar in both groups.…”
Section: Discussionsupporting
confidence: 90%
“…In one case control study, high caffeine intake (>400 mg/day) was associated with detrusor instability on cystometric evaluation [12]. Bryant et al found a 35% reduction in voids per day and 61% reduction in occasions of urgency symptoms after one month of caffeine reduction in a randomized controlled trial [19]. Caffeine reduction may be more important for women with UI who consume higher daily levels of caffeine (1-2 cups of coffee or several glasses or cups of tea or soda daily) than women who consume lower caffeine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Little robust evidence exists on caffeine and fluid management strategies. One randomized trial found a reduction in urinary urgency and frequency with caffeine reduction, while others have found that reducing excess fluid intake is beneficial [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, their daily urinary leakage and UI episode were decreased from 42.21 ± 77.34 to 24.09 ± 40.93 and from 2.60 ± 2.65 to 1.68 ± 1.52, respectively [8]. By contrast, outcomes from a prospective randomized trial showed that reduced cafeine intake could only improve patients' symptoms of frequency and urgency signiicantly, but had no efect on reduction of urinary leakage [9]. A prospective cohort study further revealed that cafeine reduction could not decrease the risk of UI progression over 2 years [10].…”
Section: Dietary Modiicationsmentioning
confidence: 97%